MATERNAL CARRIAGE AND NEONATAL COLONIZATION OF GROUP-B STREPTOCOCCI IN LABOR ARE UNCOMMON IN TURKEY - AYATA, A; GUVENC, H; FELEK, S; AYGUN, AD; KOCABAY, K; BEKTAS, S (Blackwell Science Ltd, 1994)
Group B streptococcus infection is an important cause of neonatal morbidity and mortality. We studied 114 women and their newborns to determine the relationship between maternal carriage and neonatal group B streptococcal colonisation. Rectal, cervical and vaginal swabs were taken at delivery. Within a few minutes of birth, swab specimens were also taken from throat, ear, umbilicus, conjuctiva and skin of the newborns. Group B streptococcus was isolated in 10 (8.7%) of the 114 pregnant women studied and in five (4.3%) of the 114 newborns. Vertical transmission rate was found to be 50%. Neonatal group B streptococcus colonisation has not reached a high level in Turkey, and consequently does not warrant intrapartum screening at the moment.
Keywords: Colonization; Pregnancy; Chemoprophylaxis; Infection; Disease; Women